PEMBUATAN BIOETANOL DARI BUAH SUKUN (Artocarpus altilis) SECARA FERMENTASI DENGAN MENGGUNAKAN Saccharomyces cerevisae DAN PENAMBAHAN AMPAS TAHU SEBAGAI SUMBER NUTRISI BAGI MIKROBA - Fajariah Fajariah (PROSIDING SEMINAR KIMIA, 2020)
Research on the manufacture of bioethanol from breadfruit (Artocarpus altilis ) starch by fermentation using Saccharomyces cerevisae and adding tofu pulp as a nutrient for microbes. This research was conducted to determine the nutrient concentrasiton and fermentation time to produce the optimum ethanol concentration. The hydrolysis process is carried out enzymatically through the liquefaction phase using É‘-amylase saccharification and gluko-amylase phases. The fermentation procces is carried out by a nurient source. The variation of tofu dregs used was 0,75%,1,5% and 2,25% (b / v ) and the variation of fermentation time was (6,8 and 10) days. The destillations process obtained the most distillate results on the 6th day with the addition of tofu dregs as much as 0,75% namely 18,4 ml. Keywords : Bioethanol, tofu pulp, breadfruit (Artocarpus altilis) hydrolisis